The feasibility of a road vehicle mounted aerodynamic testing apparatus - Adams, Jordan (Department of Mechanical Engineering, 2014)
A ground vehicle mounted aerodynamic testing apparatus has been identified as a candidate concept for a low-cost alternative to traditional techniques. This dissertation explores the feasibility of a ground vehicle based system by identifying physical and practical issues facing such a system. The focus is on the two most important physical problems facing the concept. These are: the ride dynamics of a vehicle as it traverses a road, and the extent of the distortion of the airflow around a vehicle. Each of these problems is quantified using approximate methods in order to estimate their influence on the testing of the aircraft in order to determine if the concept is workable.